Analisis Surat Edaran ATR/BPN Nomor 5/SE-400.HK.02/II/2022 Terkait Penetapan Hak Dan Pendaftaran Tanah Terhadap Sistem Hukum Ketatanegaraan Indonesia - Zainuddin, Nur Adilah (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
This study aimed to analyze the position of the circular letter of ATR/BPN regarding the hierarchy of laws and regulations implications of the legal ATR/BPN circular letters on the determination of rights and land registration in Indonesian constitutional system. This type of research was normative research. The results of this study indicated that 1) ATR/BPN Circular letter on the Directorate General of Land Rights Determination and Registration Number 5/SE-400.HK.02/II/2022 as a follow-up to Presidential Instruction Number 1 of 2022 concerning Optimization of National Health Insurance was basically not products of laws and regulations as stipulated of Law Number 12 of 2011 in conjunction with Law Number 13 of 2022 concerning the Formation of Legislation, so that the regulatory and binding nature of their positions could be said to be contrary to laws and regulations invitation. 2) Circular Letter of Directorate General of ATR/BPN for Determination of Rights and Registration of Land Number 5/SE-400.HK.02/II/2022 was not included as a legal norm, it have been implicated for not being able to be tested through a judicial review and this could also be categorized as a form of government arbitrariness (abuse of power).